WAYS TO SPREAD COVID 19 INFECTION (Academicia Globe: Inderscience Research, 2023)
Coronaviruses are a family of viruses that can cause illnesses such as the common cold, severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS). In 2019, a new coronavirus was identified as the cause of a disease outbreak that originated in China.